1998
DOI: 10.1086/516369
|View full text |Cite
|
Sign up to set email alerts
|

Primary Liver Abscess Due toKlebsiella pneumoniaein Taiwan

Abstract: Pyogenic liver abscess is an uncommon complication of intra-abdominal or biliary tract infection and is usually a polymicrobial infection associated with high mortality and high rates of relapse. However, over the past 15 years, we have observed a new clinical syndrome in Taiwan: liver abscesses caused by a single microorganism, Klebsiella pneumoniae. We reviewed 182 cases of pyogenic liver abscess during the period September 1990 to June 1996; 160 of these cases were caused by K. pneumoniae alone, and 22 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
483
3
11

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 552 publications
(535 citation statements)
references
References 11 publications
28
483
3
11
Order By: Relevance
“…First reported from Taiwan as a solitary organism in PLA [4], in recent studies Klebsiella pneumoniae was recognized as the leading pathogen of PLA in Asia and Western countries [2,3]. Furthermore, it was found to be associated with Asian ethnicity, diabetes mellitus and cryptogenic liver abscesses [2,3,5].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First reported from Taiwan as a solitary organism in PLA [4], in recent studies Klebsiella pneumoniae was recognized as the leading pathogen of PLA in Asia and Western countries [2,3]. Furthermore, it was found to be associated with Asian ethnicity, diabetes mellitus and cryptogenic liver abscesses [2,3,5].…”
Section: Resultsmentioning
confidence: 99%
“…Some studies showed a better prognosis for patients with Klebsiella-associated PLA than for other bacterial liver abscesses [4,9]. However, a higher incidence of metastatic infections at other sites was shown in patients with Klebsiella related PLA [9].…”
Section: Resultsmentioning
confidence: 99%
“…25,26 However, Asian series have reported Klebsiella to be the most frequently isolated bacteria. [27][28][29][30] CECT abdomen was performed in 13 cases in present series and showed no additional benefit. Amoebic serology was performed, because of endemicity of amoebiasis in our region and because of financial constraints, as most of our patens belonged to poor economic status, comparable with the available studies.…”
Section: Discussionmentioning
confidence: 99%
“…These are known as cryptogenic abscesses. [9][10] Certain risk factors for abscess development have been described, including recent bowel surgery, diabetes, alcoholism and other immuno-compromised states such as human immunodeficiency virus infections. The most frequently isolated bacteria on pus culture was Escherichia coli (44%) closely followed by Klebsiella species (33%).…”
Section: Discussionmentioning
confidence: 99%